Structure of late summer phytoplankton community in the Firth of Lorn (Scotland) using microscopy and HPLC-CHEMTAX. (20th December 2015) - Brito, Ana C.; Sá, Carolina; Mendes, Carlos R.; Brand, Tim; Dias, Ana M.; Brotas, Vanda; Davidson, Keith
Abstract: The Firth of Lorn is at the mouth of one of Scotland's largest fjordic sea lochs, Loch Linnhe. This sea loch, which is fed by a number of other inner lochs, supplies a significant flow of freshwater, which frequently causes the stratification of the water column. To investigate how environmental conditions influence the spatial distribution of phytoplankton in this region water samples were collected for phytoplankton (pigments and microscopy), and other environmental variables including nutrients. Chemotaxonomy was used to estimate the contribution of different taxonomic groups to total chlorophyll a (phytoplankton biomass index). Good agreement was obtained between chemotaxonomy and microscopy data. The highest levels of chlorophyll a (∼2.6 mg m −3 ) were found in the vicinity of Oban Bay, where cryptophytes, the most abundant group, dinoflagellates and other flagellates thrived in the stratified water column. Centric diatoms, mainly Chaetoceros sp. and Skeletonema costatum, were associated with NH4 and SiO2 concentrations and stratification, while pennate diatoms, mainly Cylindrotheca sp. and Nitzchia sp., were found to be associated with NO3 + NO2 and high surface mixed layer depths. Four diatom groups were identified in accordance to their surface to volume ratios, as well as their affinity to environmental parameters (nutrients) and turbulence. This study used a combination of physico-chemical data, classical microscopy methods (appropriate for large cells > 20 μm) and HPLC-CHEMTAX approaches (for large and small cells) to evaluate the distribution of phytoplankton functional groups in a fjordic coastal area.